1980
DOI: 10.1161/01.cir.62.6.1165
|View full text |Cite
|
Sign up to set email alerts
|

The physiologic effects of digoxin under steady-state drug conditions in newborn and adult sheep.

Abstract: The physiologic response to the chronic administration of digoxin was studied in 12 adult and 13 newborn sheep. Vascular pressures, cardiac output, isovolumic contraction phase indexes and systolic time intervals were measured before and after 2 weeks of digoxin therapy. Physiologic measurements were correlated with drug levels in plasma and myocardium. Resting myocardial function in newborns exceeded that in ewes. In ewes, the heart rate decreased from 98 to 74 beats/min, the preejection period (PEP) decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…No correlation could be found between serum potassium concentrations and fractional excretion of potassium or sodium. DISCUSSION A variety of animal studies has documented less sensitivity of the newborn to digitalis when compared to adults (4,5,12). Achieving either clinical or toxic effects of digitalis requires larger doses of the glycosides in the immature animal.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…No correlation could be found between serum potassium concentrations and fractional excretion of potassium or sodium. DISCUSSION A variety of animal studies has documented less sensitivity of the newborn to digitalis when compared to adults (4,5,12). Achieving either clinical or toxic effects of digitalis requires larger doses of the glycosides in the immature animal.…”
Section: Resultsmentioning
confidence: 96%
“…Achieving either clinical or toxic effects of digitalis requires larger doses of the glycosides in the immature animal. Such discrepancy can be partially explained by a higher clearance rate of digoxin during development; however, in several studies the lesser sensitivity to the glycoside could be demonstrated even when serum concentrations were maintained at similar levels in young and adult animals (4). No such studies are available in humans and it is highly questionable whether higher doses are needed in infants to achieve a clinical response.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in animals (19,20) and man (15) have emphasized the difficulties of evaluating glycoside effects on the myocardial contractile state in some circumstances. Moreover, because clinical benefit does not always coincide with a demonstrable improvement in myocardial function (15), the possibility of a salutary noninotropic mechanism was pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because the high resting level of myocardial muscle function early in life may not be affected adversely by structural cardiac defects (1 1-14), some have questioned the appropriateness of inotropic therapy for this patient group. Nevertheless, clinical impression and a few selected studies suggest that young subjects with structural cardiac defects benefit from cardiac glycoside therapy (15)(16)(17), although the precise mechanism of the effect has not been established (18)(19)(20).Despite the presence of vigorous myocardial muscle function with many congenital cardiac defects, the congested circulatory state can perturb oxygen transport to the tissues (15, 21). It is possible that in this setting cardiac glycosides may exert their predominant influence on the peripheral supply and demand for oxygen through their effect on the energy requiring sodiumpotassium ATPase pump enzyme system.…”
mentioning
confidence: 99%
See 1 more Smart Citation